Analysis of Genetic Variations in VP53 Gene Sequences cause Broad bean wilt virus in Chili (Capsicum annuum) NCBI Popset 2505221052 Using In-Silico RFLP - Ramadhani, Mutiara (Jurnal Serambi Biologi, 2023)
Chilli is a plant that can be grown in a temperature range of 21oC - 27oC, so chilli can grow in lowland areas. The high-low temperature of chilli growth can cause plant growth to be disrupted. Chilli plants are often susceptible to diseases, one of which is long bean wilt disease caused by the VP53 virus. How to detect genetic variation in chilli with RFLP. In this study, the gene sequence used was VP53. Screening of restriction enzyme candidates that will be used in silico.ehu. RFLP using benchling tools. RFLP results on 2 chilli VP53 gene sequences were cut using the restriction enzyme MslI. Based on table 2, it is known that the total DNA bands amplified at fragment sizes of 1.3 kb, 989 bp, and 406 bp are as many as 4 DNA bands with each amplified fragment size. Based on the results it can be concluded that the genetic variation of the VP53 gene by bringing up 2 DNA bands of the same size according to NCBI with popset number 2505221052.